E_CRITOR_S - Morais, Fabio dos Santos (2021)
E_CRITOR_S is an essay on the different forms that writing adopts when adapting to the materialities and spaces of art. Analyzing various works of contemporary art that have the verbal text as the axis and also translating a text-work, this essay is like a walk through an exhibition space, focusing on the specifics of a writing that can be considered as “moving linguistic matters in three-dimensional space”, in addition to register articulations of thoughts or narratives in the verbal texture.